ECONOMICS OF THE COMMON MIXTURE OF MIXED CROPPING IN THE SEMI-ARID TRACT OF CENTRAL RAJASTHAN - Jain, K C; Bajpai, M R (Annals of Arid Zone, 2016)
An experiment was conducted at the College of Agriculture Farm,Jobner to compare the economics of cultivation and net profit receivedthrough various crop mixtures (1/2 : 1/2)) in kharif, 1969. The results aresummarised as follows.Among the various crop mixtures maximum net profit was recordedwith the mixture bajra + guar.In different mixtures of til + legumes the maximum profit wasrecorded with til + guar followed by til + cowpea.Bajra alone produced a net profit of Rs. 1J67/ha which was Rs,330/ha more than til alone. This profit could be compared withthe mixtures of bajra +-moth and bajra + moong, but not withbajra + cowpea (net profit Rs. 737{ha only).For taking higher net profit through mixed cropping guar should beprefered among the associated crops (legumes) and bajra among themain crops.Bajra + guar was the best crop mi"ture for getting the maximumnet profit. Bajra + moong should be prefered over bajra alone as theprofits are comparable but the soil fertility could better be maintained inbajra legume mixture than bajra alone.